Integration of Design Thinking in Strengthening the Circular Economy Model: A Systematic Literature Review on Sustainable Innovation Practices | (Versi en lama): Integration of Design Thinking in Strengthening the Circular Economy Model: A Systematic Literature Review on Sustainable Innovation Practices - Muhammad Rizal; Aminuddin Hamdat; Muh. Ridwan; Megawaty Megawaty (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research is motivated by the limited number of studies integrating Design Thinking, Circular Economy, and Sustainable Innovation within a single conceptual framework for sustainability innovation. However, these three approaches have the potential to support more sustainable and human-centered organizational transformation. This study aims to identify dominant themes, conceptual relationships, research trends, and literature gaps related to the integration of these three concepts. The method used is a Systematic Literature Review with the PRISMA 2020 framework and bibliometric analysis using VOSviewer on 55 articles published between 2010 and 2025. The results show that sustainability innovation studies are still dominated by the themes of resource efficiency, sustainable manufacturing, and industrial process optimization. However, the development of themes such as human-centered design, stakeholder engagement, Industry 5.0, and collaborative innovation ecosystems indicates a shift towards a more participatory sustainability paradigm. This study concludes that Design Thinking plays a role as an approach capable of connecting technology-based sustainability goals with collaborative innovation processes. These findings contribute to strengthening the conceptual framework for sustainability innovation and provide implications for the development of more inclusive organizational transformation strategies.